A New Functional Approach to Scientific Progress. - Shan, Yafeng (Philosophy of Science, 2019)
This article develops and defends a new functional approach to scientific progress. I begin with a review of the problems of the traditional functional approach. Then I propose a new functional account of scientific progress, in which scientific progress is defined in terms of usefulness of problem defining and problem solving. I illustrate and defend my account by applying it to the history of genetics. Finally, I highlight the advantages of my new functional approach over the epistemic and semantic approaches and dismiss some potential objections to my approach.